Clean Cut (adaptive, multimodal surgical infection prevention programme) for low‐resource settings: a prospective quality improvement study. Issue 6 (21st September 2020) - Forrester, J A; Starr, N; Negussie, T; Schaps, D; Adem, M; Alemu, S; Amenu, D; Gebeyehu, N; Habteyohannes, T; Jiru, F; Tesfaye, A; Wayessa, E; et al.
Abstract : Clean Cut is a multimodal, adaptive, checklist‐based infection prevention programme designed to improve compliance with six critical perioperative infection prevention practices. After introducing the programme at five hospitals in Ethiopia, compliance with critical infection prevention standards significantly improved and the relative risk of infection fell by 35 per cent. keep it simple Abstract: Background: Clean Cut is an adaptive, multimodal programme to identify improvement opportunities and safety changes in surgery by enhancing outcomes surveillance, closing gaps in surgical infection prevention standards, and strengthening underlying processes of care. Surgical‐site infections (SSIs) are common in low‐income countries, so this study assessed a simple intervention to improve perioperative infection prevention practices in one. Methods: Clean Cut was implemented in five hospitals in Ethiopia from August 2016 to October 2018. Compliance data were collected from the operating room focused on six key perioperative infection prevention standards. Process‐mapping exercises were employed to understand barriers to compliance and identify locally driven improvement opportunities. Thirty‐day outcomes were recorded on patients for whom intraoperative compliance information had been collected. Results: Compliance data were collected from 2213 operations (374 at baseline and 1839 following process improvements) in 2202 patients. Follow‐up was completed in 2159 patients (98·0 per cent). At baseline, perioperative teams complied with a mean of only 2·9 of the six critical perioperative infection prevention standards; following process improvement changes, compliance rose to a mean of 4·5 ( P < 0·001). The relative risk of surgical infections after Clean Cut implementation was 0·65 (95 per cent c.i. 0·43 to 0·99; P = 0·043). Improved compliance with standards reduced the risk of postoperative infection by 46 per cent (relative risk 0·54, 95 per cent c.i. 0·30 to 0·97, for adherence score 3–6 versus 0–2; P = 0·038). Conclusion: The Clean Cut programme improved infection prevention standards to reduce SSI without infrastructure expenses or resource investments.